Risk factors for prolonged intensive care unit stays in patients after cardiac surgery with cardiopulmonary bypass: A retrospective observational study - Xueying Zhang; Wenxia Zhang; Hongyu Lou; Chuqing Luo; Qianqian Du; Ya Meng; Xiaoyu Wu; Meifen Zhang (Elsevier, 2021)
Objectives: Patients after cardiac surgery with cardiopulmonary bypass (CPB) require a stay in the ICU postoperatively. This study aimed to investigate the incidence of prolonged length of stay (LOS) in the ICU after cardiac surgery with CPB and identify associated risk factors. Methods: The current investigation was an observational, retrospective study that included 395 ICU patients who underwent cardiac surgery with CPB at a tertiary hospital in Guangzhou from June 2015 to June 2017. Data were obtained from the hospital database. Binary logistic regression modeling was used to analyze risk factors for prolonged ICU LOS. Results: Of 395 patients, 137 (34.7%) had a prolonged ICU LOS (>72.0 h), and the median ICU LOS was 50.9 h. Several variables were found associated with prolonged ICU LOS: duration of CPB, prolonged mechanical ventilation and non-invasive assisted ventilation use, PaO2/FiO2 ratios within 6 h after surgery, type of surgery, red blood cell infusion during surgery, postoperative atrial arrhythmia, postoperative ventricular arrhythmia (all P < 0.05). Conclusions: These findings are clinically relevant for identifying patients with an estimated prolonged ICU LOS, enabling clinicians to facilitate earlier intervention to reduce the risk and prevent resulting delayed recovery.